THE EFFECT OF ONLINE LEARNING AND STUDENT MOTIVATION DURING THE COVID-19 PANDEMIC - geta septiadi; Firmansyah Dliss; Abdul Sukur (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2021)
The purpose of this study was to obtain information about the effect of online learning media learning and student motivation during the Covid-19 pandemic on physical education learning outcomes. The method in this study uses Path Analysis. The sample included in this study amounted to 161 students. The results of the analysis show that the contribution of the influence of Online Learning (X1) on Learning Outcomes (Y) is significant at 0.807, Learning Media (X2) on Learning Outcomes (Y) is significant at 0.783, Motivation (X3) on Learning Outcomes (Y) which significant at 0.834, Online Learning (X1) on Motivation (X3) which is significant at 0.532, Media Learning (X2) on Motivation (X3) which is significant for 0.614. The conclusion in this study is that online learning, learning media and motivation have a direct effect on physical education learning outcomes during the COVID-19 pandemic. Online learning, learning media have a direct effect on motivation in students during the COVID-19 pandemic.